Pengaruh Citra Merek, Kualitas Produk dan Promosi Terhadap Keputusan Pembelian Pada Produk Skincare Avoskin - Nenik Diah Hartanti; Hendri Rahmayani Asri; Ekaning Setyarini; Budi Santoso (ARBITRASE: Journal of Economics and Accounting, 2024)
The skincare business is currently growing rapidly. With more and more new skincare brands emerging, the competition among skincare product entrepreneurs is becoming increasingly fierce. The purpose of this research is to determine and analyze the influence of brand image, product quality, and promotion on the purchasing decisions of Avoskin skincare products both simultaneously and partially. The research method used is quantitative. The population in this study consists of female consumers who have purchased Avoskin skincare products at least once. The sample size set is 150 respondents. The analysis method in this research uses primary quantitative data, with the following tests conducted: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, T-test, F-test, and coefficient of determination using SPSS statistical testing tools. The sampling method used in this research is non-probability sampling with a purposive sampling technique. The results of the study show that partially, the Brand Image variable affects the Purchasing Decision with a significance value of 0.000 < 0.05 or a t-value of 3.854 > t-table of 1.984. Product Quality affects the Purchasing Decision with a significance value of 0.001 < 0.05 or a t-value of 3.558 > t-table of 1.984. Promotion partially affects the Purchasing Decision with a significance value of 0.000 < 0.05 or a t-value of 5.297 > t-table of 1.984. Simultaneously, Brand Image, Product Quality, and Promotion affect the Purchasing Decision with a significant value of 0.000 < 0.05.